Uncovering the Key Factors Behind Junior College Students’ Satisfaction and Commitment to E-Learning in Jiangxi, China - Zhang, Shiqi (Scholar: Human Sciences, 2025)
Purpose: This study thoroughly examines the factors influencing junior college students’ satisfaction and continued intention to engage in e-learning in Jiangxi, China. Research design, data, and methodology: To gather statistical data, it is recommended to survey university students in Jiangxi, China, who have experience with e-learning. The collected data was analyzed using Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) to assess the relationships between variables. For this research, a sample size of 500 junior college students was selected to ensure a more comprehensive understanding of the study. Results: E-learning platforms feature continuous updates and optimization of course content, ensuring that learners can keep pace with the times and access cutting-edge educational resources and research findings. This acknowledgment of course content significantly enhances learners’ trust and satisfaction, stimulating their enthusiasm for learning. E-learning offers a wide variety of course options and customizable learning paths, allowing learners to feel that their investment is well-rewarded and strengthening their recognition of the value of online learning. Conclusions: The study discovered that students’ perceptions of interaction favorably impact their perceptions of confirmation, contentment, and perceived usefulness, all of which are directly related to their desire to stick with the system.